Effective Teaching in a Humanities and Languages Foundation Year: Lessons Learned from Teaching During a Pandemic. - Hewertson, Helen (PRISM: Casting New Light on Learning, Theory and Practice, 2024)
This paper will explore key research around Foundation year entry at a large Northwest university in England, UK and explore what makes effective provision. It will share lessons learned during Covid-19 from student feedback from a Humanities, and Languages foundation year. There is some research around what makes for a successful foundation year. This has not had the attention it deserves, and there are still only a few papers based in the UK context. The paper explores and discusses key aspects that make a foundation entry programme successful. Furthermore, the paper explores the experiences of students from non-traditional backgrounds, (or with non-standard qualifications), and how they can underperform in comparison to students with more traditional academic backgrounds, i.e., those that have successfully passed standard Advanced Levels. In relation to non-traditional students, a good Foundation Year can help improve the outcomes for these students, and offer them opportunities to be as successful – or indeed more successful – than traditional entry students.